QUINOLIN-6-AMINES: SYNTHESIS AND BIOLOGICAL EVALUATION - Hament Panwar; Nidhi Chaudhary; Ranjana Dubey; Tilak Ram (Universitas Gadjah Mada, 2013)
Some novel 2-(chloromethoxy)methylthio-N-substituted phenyl-[1,2,4]triazolo[1,5-a] quinolin-6-amines have been derived from 5-bromocoumarin. All the synthesized compounds have been characterized by elemental and spectral (I.R., 1H-NMR, Mass) analysis and evaluated for their antimicrobial, insecticidal and anthelmintic activities.